HUBUNGAN PENCANTUMAN PESAN GAMBAR PADA BUNGKUS ROKOK DENGAN PERUBAHAN PERILAKU MASYARAKAT DI PROVINSI SUMUT - Yusuf Hanafi Lubis; Linda Mutiara Harahap; Ivena Hotmarina Septiani Nainggolan (Jurnal Kesehatan Masyarakat, 2022)
Indonesia has 60.8 million adult male smokers and 3.7 million adult female smokers. Basic Health Research in 2018 showed that 62.9% of men and 4.8% of women aged 15 years and over use tobacco. The objectives of this study was to find out how much people's behavior changes after seeing the inclusion of image messages on cigarette packs. Research methods use a quantitative approach with cross sectional study design. The study was conducted in North Sumatra province in July - August 2021. The population in this study is a society aged 10-65 years with a sample number representing a population of 1178 people with purposive sampling data analysis techniques using univariate analysis and bivariate chi square test analysis with a confidence value of 95% and 5% meaning. The results showed that sex was dominated by 782 men (66.4%), while women only got 396 people (33.6%). Chi square test results on dependent and independent variables (p = 0.048), disgust (p = 0.032), feel like swapping cigarette packs (p = 0.005), and feel trust (p = 0.058). The conclusion is that the statistical test using the chi square test method obtained p = 0.048 < α = 0.05, it can be concluded that there is a relationship between fear of the inclusion of image messages on cigarette packs with changes in behavior. The suggestions for smokers is to stop smoking because smoking is not only detrimental to yourself but also others who are around, namely with cigarette smoke that you emit.